2021
DOI: 10.1021/acs.nanolett.0c04687
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with a Self-Assembled Nanoparticle Vaccine Elicits Potent Neutralizing Antibody Responses against EBV Infection

Abstract: Epstein–Barr virus (EBV) infection is a global health concern infecting over 90% of the population. However, there is no currently available vaccine. EBV primarily infects B cells, where the major glycoprotein 350 (gp350) is the main target of neutralizing antibodies. Given the advancement of nanoparticle vaccines, we describe rationally designed vaccine modalities presenting 60 copies of gp350 on self-assembled nanoparticles in a repetitive array. In a mouse model, gp350s on lumazine synthase (LS) and I3-01 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 41 publications
3
23
1
Order By: Relevance
“…In addition, injecting Cynomolgus macaques with gp350D 123 -LS resulted in higher antibody titers than gp350D 123 . Nanoparticles combined with the adjuvant MF59 stimulated a more robust humoral response than nanoparticles combined with the adjuvant aluminum hydroxide [ 203 ].…”
Section: Advances In Ebv Antiviral Therapymentioning
confidence: 99%
“…In addition, injecting Cynomolgus macaques with gp350D 123 -LS resulted in higher antibody titers than gp350D 123 . Nanoparticles combined with the adjuvant MF59 stimulated a more robust humoral response than nanoparticles combined with the adjuvant aluminum hydroxide [ 203 ].…”
Section: Advances In Ebv Antiviral Therapymentioning
confidence: 99%
“…Lastly, Kang et al (2021) demonstrated the immunogenicity of the first 425 residues of the gp350/220 ectodomain expressed on two different self-assembled nanoparticles that mimic the shape and size of EBV: lumazine synthase (LS) and I3-01, two capsid-forming enzymes. The gp350/220 1−425 -LS and gp350/220 1−425 -I3-01 nanoparticles adjuvanted with aluminum hydroxide or MF59 elicited in mice over 133-and 65-fold higher neutralizing antibody titers, respectively, than that induced by the corresponding gp350 monomer (Kang et al, 2021). Cui et al, 2013;1b, Kanekiyo et al, 2015;1c, Zhao et al, 2018;1d, Zhang et al, 2020;1e, Kang et al, 2021;2a,2b, Cui et al, 2016;2c, Cui et al, 2021;2d, Bu et al, 2019;2e, Escalante et al, 2020;3, Elliott et al, 2008;4a,4b, Perez et al, 2017;4c, van Zyl et al, 2018. While these new strategies have yet to be compared with one another, all of them seem to be more immunogenic than soluble gp350 monomers and represent promising attempts to enhance the immunogenicity of anti-gp350/220 vaccines.…”
Section: Optimization Of the Prophylactic Vaccinesmentioning
confidence: 99%
“… Optimization of prophylactic vaccine strategies. 1a, Cui et al, 2013 ; 1b, Kanekiyo et al, 2015 ; 1c, Zhao et al, 2018 ; 1d, Zhang et al, 2020 ; 1e, Kang et al, 2021 ; 2a,2b, Cui et al, 2016 ; 2c, Cui et al, 2021 ; 2d, Bu et al, 2019 ; 2e, Escalante et al, 2020 ; 3, Elliott et al, 2008 ; 4a,4b, Perez et al, 2017 ; 4c, van Zyl et al, 2018 . …”
Section: Optimization Of the Anti-ebv Vaccine Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is reasonable to make gp350 the primary target for vaccine development ( 11 ). By incorporating gp350 into different forms of carriers, such as monomers ( 12 ), oligomers ( 13 , 14 ), nanoparticles ( 15 , 16 ), vaccinia viruses ( 17 ), recombinant adenoviruses ( 18 ), varicella-zoster viruses (VZVs) ( 19 ), and Newcastle disease viruses (NDVs) ( 20 , 21 ), many gp350-centered vaccines have emerged. To date, however, clinical trials of gp350-centered vaccines have shown no protection against EBV infection ( 22 ).…”
Section: Introductionmentioning
confidence: 99%